Meningkatkan Kesadaran Anggota KSPPS BMW Rahmah Jatim Dalam Menunaikan Wakaf Uang Melalui Sosialisasi Dan Gerakan Kaleng Shodaqoh Subuh - Latifah, Nur Asiah Binti; Lestari, Diyah Ayu; Intani , Adelia Septi Dewi; Sari, Ilma Nofita; Janah, Sidanatul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Through the dissemination and implementation of this dawn can shodaqoh movement, it is hoped that the literacy index of cooperative members in carrying out ZISWAF will be higher. The implementation of the activities carried out during the RAT activities took place at the WSG (Warung Setono Goerih) on Jl. Untung Suropati no. 14-22, Pakelan Kediri City, namely increasing the awareness of cooperative members in carrying out ZISWAF, which was carried out in 3 stages of implementation and received appreciation and a good response. In preparation for the implementation, surveys and preparatory discussions were carried out, namely to determine the place and time of implementation. Then, in the early stages of its implementation, socialization of the introduction of ZISWAF was carried out through ZISWAF introduction material. Furthermore, the implementation of the Shodaqoh Movement The implementation was carried out by gathering KSPPS BMW Rahmah East Java members, whose proceeds were distributed to compensation for orphans, educational, social, and religious expenses, and Qordul Hasan financing.